Income Perspectives In The Coconut Sugar Industry A Comparative Study Of Landowner Farmers And Tenant Farmers In Labuhan Ratu - Syaiful Bakhri; Hikmatul Aliyah; Putri Sandora; Nurul Muslimah (Utan Kayu Publishing, 2024)
The plantation sub-sector is an important part of national development. One of the plantation commodities widely managed by small industries is coconut sugar, with raw materials derived from coconut trees. In Labuhan Ratu District, many small household industries are engaged in the production and processing of coconut sugar. This processing is done using coconut plants that have not been intensively cultivated. It is known that the average cost incurred by tenant farmers and landowner farmers is IDR 96,000 per week, with a production output of 1 quintal of brown sugar and a rental cost of IDR 70,000 per tree per year. This study aims to determine the income differences between landowner farmers and tenant farmers in the coconut sugar business in Labuhan Ratu District, East Lampung. The data collection techniques used include observation, documentation, and interviews. The study population consists of 100 coconut sugar entrepreneurs in Labuhan Ratu District, with the same sample size using the saturated sampling technique. Data analysis results show that at a 5% error level with 98 degrees of freedom, the t-table value is 1.66055, while the calculated t-value is 2.770. Because the calculated t-value (2.770) t-table value (1.66055), the alternative hypothesis (Ha) is accepted, meaning there is a difference in income between landowner farmers and tenant farmers in the coconut sugar business in Labuhan Ratu District, East Lampung. Landowner farmers have higher incomes than tenant farmers because the income of tenant farmers must be shared among group members or partnerships, whereas the income of landowner farmers is entirely owned by one individual.